The effects of whole body immersion in cold water upon subsequent terrestrial aerobic performance : a study in hypothermia - Manley, Elizabeth (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 1998)
This study examined the extent to which physiological and psychological concomitants of aerobic terrestrial performance were affected by body cooling of varying degrees induced by cold water immersion (CWI). Thirteen male and 13 female subjects underwent three randomly assigned 30 min treadmill runs: a control run without prior manipulation of the subjects' thermal status and the same exercise after "central" (core temperature 1Â°C below pre-immersion) and "peripheral" cooling (skin heat loss 100kcal.mâ »Â².hâ »Â¹). During treadmill runs core temperature was measured, together with chest, leg, arm and hand temperatures, from which mean skin temperature (T [subscript]s[subscript]k) and mean body temperature (T[subscript]b) were calculated. Heart rate, oxygen consumption (VOâ‚‚,), carbon dioxide production (VCOâ‚‚), minute ventilation (Vâ‚‚ (BTPS)), breathing frequency (f), cadence and ratings of perceived exertion (RPE) and thermal sensation (PTS) were also measured. Both central and peripheral cooling resulted in significantly reduced T[subscript]r[subscript]e (males : control 37.9Â±0. 3Â°C; central cooling : 36.8Â±0.5Â°C; peripheral cooling: 37.5Â±0.4Â°C; females: control: 37.9Â±0.4Â°C; central cooling: 37.2Â±0.5; p<0.05) during subsequent treadmill running, except following peripheral cooling for females (37.9Â±0.3Â°C) . For males and females T[subscript]s[subscript]k was lower following peripheral cooling than control values and lowest after central cooling (males: control: 30.0Â±1.3Â°C; central cooling: 36.8Â±0.5Â°C; peripheral cooling: 37.5Â±0.4Â°C; females: control: 30.5Â±1.2Â°C; central cooling: 25.9Â±1.8Â°C; peripheral cooling: 26.9Â±1.9Â°C; p<0.05). Female subjects experienced significantly higher T[subscript]r[subscript]e than males following central and peripheral cooling and a lower T[subscript]s[subscript]k following central cooling. Females experienced less of an increase in heart rate than males during exercise following central and peripheral cooling (control: l57.7Â±23.7b.minâ »Â¹; central cooling: 143.5Â±20.5b.minâ »Â¹; peripheral cooling 151.7Â±16.7b.minâ »Â¹; p<0 .05). Male responses were the same following central cooling but higher for peripheral cooling than control values (control: 139.1Â±7.3b.minâ »Â¹; central cooling 134.7Â±17.5b.minâ »Â¹; peripheral cooling: 145.0Â±16.4b.minâ »Â¹; p<0.05). These data indicate a depression in cardiovascular function for females following peripheral cooling that was not apparent for males. The VOâ‚‚ was not different between tests for males; only peripheral cooling resulted in a raised VOâ‚‚ of 28.6Â±3 .3ml.kgâ »Â¹.minâ »Â¹ (p<0 .05) for females compared to 27.6Â±2.6ml.kgâ »Â¹.minâ »Â¹ (control). A biphasic response was evident for VOâ‚‚ VCOâ‚‚ and V[subscript]B (BTPS). For both sexes overall RPE was lower for peripheral cooling (males: 9.4Â±1.9; females: 8.7Â±1.3; p<0 .05) than for control and central cooling. Central RPE was only changed for females following peripheral cooling. Changes in cadence and step length together with the effect of low skin and leg temperatures resulted in higher local RPE for females after central cooling (9.6Â±1.2; p<0.05) than control (9.4Â±1.9) and peripheral cooling (8.9Â±1.2 ). Males and females rated the same ambient temperature during the same exercise lower after peripheral cooling (males: 4.6Â±1.5; females : 5.3Â±1.3) than control values and lower still after central cooling (males: 3. 8Â±1.8; females: 2 .7Â±l. 5) In this study T[subscript]s[subscript]k was the primary determinant of PTS after precooling.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Hypothermia; Cold -- Physiological effect; Temperature -- Physiological effect; Aerobic exercises; Cryobiology